Renal Transplantation in Patients With Urinary Diversion—Bypassing the Conduit: A Case Report - Matthew D. Wainstein; Obi Ekwenna (Case Reports in Transplantation)
Kidney transplantation in patients with supravesical urinary diversions is a relatively rare procedure. The typical approach for establishing urinary drainage in these patients is through an ureteroileal anastomosis. However, a tension-free ureteroileal anastomosis can be difficult to achieve based on variations in the anatomy of the donor ureter or recipient conduit. An alternative technique can be to create an anastomosis between the donor and recipient ureter, although reports of this technique in the last 20 years have been sparse. Here, we present two cases of patients with prior ileal conduits who underwent successful renal transplantation with uretero-uretero anastomoses.